2003
DOI: 10.1046/j.1365-2672.2003.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

An antifungal compound produced by Bacillus subtilis YM 10-20 inhibits germination of Penicillium roqueforti conidiospores

Abstract: Aims: To identify and characterize an antifungal compound produced by Bacillus subtilis YM 10-20 which prevents spore germination of Penicillium roqueforti. Methods and Results: The antifungal compound was isolated by acid precipitation with HCl. This compound inhibited fungal germination and growth. Identification by HPLC and mass spectrometry analysis showed high similarity to iturin A. Permeabilization and morphological changes in P. roqueforti conidia in the presence of the inhibitor were revealed by fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 29 publications
10
75
0
4
Order By: Relevance
“…6a and 6b). Our result was in agreement with some previous studies which reported that the antifungal compound was resistant to several proteolytic enzymes, including proteinase E, proteinase K, and chymotrypsin 32 . Balouiri et al 33 showed that the anti-candida activity of bioactive compounds pro-duced by Bacillus spp.…”
Section: Discussionsupporting
confidence: 94%
“…6a and 6b). Our result was in agreement with some previous studies which reported that the antifungal compound was resistant to several proteolytic enzymes, including proteinase E, proteinase K, and chymotrypsin 32 . Balouiri et al 33 showed that the anti-candida activity of bioactive compounds pro-duced by Bacillus spp.…”
Section: Discussionsupporting
confidence: 94%
“…The role of fengycins was demonstrated by the very effective disease control provided by treatment of fruits with cLPs-enriched extracts and by in situ detection of fengycins in inhibitory amounts (Touré et al, 2004). To further illustrate the broad range of fungal targets, fengycins were also reported for their antagonistic activity against Fusarium graminearum (Wang et al, 2007), and iturins for their inhibitory effect towards the anthracnose-causing agent Colletotrichum dematium (Hiradate et al, 2002), Penicillium roqueforti (Chitarra et al, 2003), Aspergillus flavus (Moyne et al, 2001), Rhizoctonia solani (Yu et al, 2002), wood-staining fungi (Velmurugan et al, 2009) and nematophagous fungi (Li et al, 2007). In some instances, the fungitoxic activity was clearly related to the permeabilization of spore/conidia therefore inhibiting germination or alternatively to hyphal cell perturbation.…”
Section: Direct Inhibition Of Phytopathogens 421 Antibiosis Membersmentioning
confidence: 99%
“…In some instances, the fungitoxic activity was clearly related to the permeabilization of spore/conidia therefore inhibiting germination or alternatively to hyphal cell perturbation. As revealed by transmission electron microscopy techniques, both phenomena most probably result from membrane damaging by the cLPs (Chitarra et al, 2003;Etchegaray et al, 2008;Romero et al, 2007a). A few studies have revealed some insecticide activity of cLPs from B. subtilis.…”
Section: Direct Inhibition Of Phytopathogens 421 Antibiosis Membersmentioning
confidence: 99%
“…Meanwhile, we also detected the tolerance of MHT6's antifungal compound on proteinase K, strongly acidic (pH < 5) and alkaline (pH > 11) conditions. Purification of antifungal active compound in MHT6 by FPLC: Cell-free supernatants of MHT6 were mainly extracted following the method described by (Chitarra et al, 2003). Generally speaking, strain was grown in NB medium for 3 days at 30°C with shaking at 150 rpm.…”
Section: Purification and Identification Of Antifungal Active Compounmentioning
confidence: 99%